2021
DOI: 10.35308/j-kesmas.v8i2.3385
|View full text |Cite
|
Sign up to set email alerts
|

Identify Factors Associated with Scabies Aged 6-19 Years Old in The Boarding School

Abstract: Scabies is a significant worldwide health problem in boarding school children with dangerous systemic complications and an increased risk of mortality because of low priority for treatment. The method uses systematic review. Data sources were collected from databases such as Pubmed and Google Scholar regarding the incidence of scabies in boarding schools indexed nationally and internationally in 2014 - 2019. The exhaustive literature obtained is 15 studies, totaling 2490 samples by determining the required var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
1
0
1
Order By: Relevance
“…Adult mites can exit the stratum corneum, attach to clothing, and live outside the human body for about three days, long enough to transmit scabies (27). In a systematic review of 14 studies in boarding schools in 2020, sharing of personal items was signi cantly associated with being a scabies case-person (35). Other studies have reported similar ndings (27,36).…”
Section: Discussionmentioning
confidence: 88%
“…Adult mites can exit the stratum corneum, attach to clothing, and live outside the human body for about three days, long enough to transmit scabies (27). In a systematic review of 14 studies in boarding schools in 2020, sharing of personal items was signi cantly associated with being a scabies case-person (35). Other studies have reported similar ndings (27,36).…”
Section: Discussionmentioning
confidence: 88%
“…Pendahuluan Skabies yaitu suatu kondisi kelainan kulit yang terjadi karena infeksi dari kutu sarcoptes scabiei varietas hominis dari famili sarcoptidae (1). Penyakit ini bisa menular dengan cepat lewat kontak langsung dengan para penderita skabies atau secara tidak langsung melalui penggunaan alat-alat pribadi bersamaan seperti pakaian, handuk, selimut yang telah terkontaminasi (2). Risiko penyebaran penyakit skabies biasanya sering terjadi di tempat yang padat dengan kebersihan yang tidak terjaga seperti di fasilitas penitipan anak, rumah tahanan dan pondok pesantren (3).…”
Section: Aunclassified
“…14 Masih adanya kasus penderita Scabies terutama sekolah boarding menjadi hal penting untuk melakukan penyuluhan dan edukasi tentang peningkatan kesehatan di sekolah asrama. 9,18 Menurunkan risiko kejadian penyakit ini, tim pengabdian masyarakat melakukan PADE Journal, Volume 5, Nomor 2, Oktober 2023 penyuluhan dan pendidikan kesehatan untuk meningkatkan pengetahuan, sikap dan tindakan santri untuk meningkatkan kesehatan pribadi.…”
Section: Hasil Dan Diskusiunclassified